Accounting Information System and Integrated Reporting Implementation: A Review of Literature - Tuan Hazam, Sharifah Robiah (International Journal of Accounting, Finance and Business, 2025)
Accounting information systems are tools specifically designed to collect and process financial information, enabling users to generate valuable reports. Following the changes of the Industrial Revolution level, the accounting information system has also evolved. A structured accounting information system processes financial data and provides analytical tools for enhancing future corporate performance. The trending implementation of integrated reporting supports the significance of leveraging advanced accounting information systems to provide organisations with an innovative outlook on corporate reporting. This study aims to review the accounting information systems that influence the implementation of integrated reporting. It also examines the advantages and use of accounting information systems. Furthermore, it evaluates the correlations between accounting information systems and the implementation of integrated reporting. Consequently, it is important to improve the current accounting information system or establish a new system to facilitate the successful implementation of integrated reporting. In order to bolster the current research discussion, this study also offers pertinent prior research.